If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-3p=-4p
We move all terms to the left:
5-3p-(-4p)=0
We get rid of parentheses
-3p+4p+5=0
We add all the numbers together, and all the variables
p+5=0
We move all terms containing p to the left, all other terms to the right
p=-5
| 7w+5=3w-15} | | 9.69+2.05+0.3p=–1.7p+2.14 | | 10x=7x15 | | 5/x=3- | | -6b+7-3=-8b+10 | | (2x+9)(x−5)=0 | | 1/4(z+3z)+7=−z+114(z+3z)+7=−z+1 | | 8+f=-f-10 | | -u+9=-6+4u | | -10z-10=-z+10-4z | | -10+2n=5-n | | -5t+9-6t=-7-9t | | 1/2x=1/3x+9 | | 92=4(v+13) | | 2|n+7|=|4+8| | | 6a(10)= | | 10+3q=4q | | X^2+3x÷2-1=0 | | F(x)=x(60-2x) | | X^2-3x+64=0 | | n-(-5)=-8 | | 13=11-4b | | 20=-2-a | | -3n=-3n | | 5x(-(x-18)=6-2(x+15) | | -7x-21=2(-3-x) | | 2πr=44 | | 3/4w-7=-2/3w-7/2 | | -2+7(6x-6)=26+7x | | 5x^2+4x+1500=3200 | | -9=13x-7+12 | | -112=4(4x=4) |